2009
DOI: 10.1002/art.24760
|View full text |Cite
|
Sign up to set email alerts
|

Regression of systemic lupus erythematosus after development of an acquired Toll‐like receptor signaling defect and antibody deficiency

Abstract: Toll-like receptor 9 (TLR-9) and TLR-7 may have a role in the production of anti-DNA and anti-RNA autoantibodies, respectively, but murine models do not clearly demonstrate their contribution to the development of systemic lupus erythematosus (SLE). Herein we describe a patient with SLE who had long-lasting remission of her autoimmune disease after development of an antibody deficiency resembling common variable immunodeficiency (CVID). After CVID had developed, antidouble-stranded DNA antibodies disappeared, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 16 publications
(26 reference statements)
0
17
0
Order By: Relevance
“…Several studies have demonstrated that anti-nucleic acid immune complexes, isolated from the sera of SLE patients, stimulate plasmacytoid dendritic cells (pDCs) to produce IFN-a (19,20). Mean et al (21) have reported that DNA-containing immune complexes, but not protein-containing immune complexes, stimulate pDCs to produce cytokines, including IFN-a, TNF, and IL-8.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that anti-nucleic acid immune complexes, isolated from the sera of SLE patients, stimulate plasmacytoid dendritic cells (pDCs) to produce IFN-a (19,20). Mean et al (21) have reported that DNA-containing immune complexes, but not protein-containing immune complexes, stimulate pDCs to produce cytokines, including IFN-a, TNF, and IL-8.…”
Section: Discussionmentioning
confidence: 99%
“…IFNα is critical player in SLE progression and severity, and has been shown to induce the production of autoantibodies when administered to non-SLE patients (12, 51). An interesting report describes remission of SLE in a patient which was attributed to unresponsiveness to both TLR-7 and -9 stimulation after development of common variable immunodeficiency – (CVID-) like disease (52). Genetic variations in many of the components of the TLR signaling pathway have been associated with SLE, such as TLR-7, IRF5, IRF7, IRF8, IRAK1, and TNFAIP3 (5359).…”
Section: Genetic Factors Associated With Tlr-dependent Ifnα Pathway Imentioning
confidence: 99%
“…Furthermore, IVIG attenuates Toll-like receptor 9 (TLR9) responses through the recruitment of the inhibitory SHP-1 phosphatase [36]. Inhibition of TLR9-mediated B cell activation could be an important mechanism of the immunoregulatory effects of IVIG in autoimmune disorders [37,38].…”
Section: Discussionmentioning
confidence: 99%